2017
DOI: 10.4103/2249-4863.214961
|View full text |Cite
|
Sign up to set email alerts
|

Acanthosis nigricans: A screening test for insulin resistance – An important risk factor for diabetes mellitus type-2

Abstract: Background:Acanthosis nigricans (AN) is one of the signs suggestive of high insulin resistance (IR). IR is one of the mechanisms involved in pathogenesis of diabetes mellitus type-2 (DM Type-2). Thus, early detection of IR in children may allow us time to intervene well before the development of DM Type-2. In this study, 62% of children having AN had high IR. In children having both, AN and high body mass index (BMI), the incidence of IR was about 80%. This suggests that these easily detectable parameters alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Several previous studies from India have investigated association between these cutaneous signs of IR in isolation with different facets of MetS like anthropometric measures of obesity (i.e., BMI [32], waist circumference [37,38], W:H ratio), HOMA-IR [29,30,31,33], lipid parameters, diabetes and other diseases clustering with MetS [34,35,36]. They all nd an association between these cutaneous signs and the facets of MetS they investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies from India have investigated association between these cutaneous signs of IR in isolation with different facets of MetS like anthropometric measures of obesity (i.e., BMI [32], waist circumference [37,38], W:H ratio), HOMA-IR [29,30,31,33], lipid parameters, diabetes and other diseases clustering with MetS [34,35,36]. They all nd an association between these cutaneous signs and the facets of MetS they investigated.…”
Section: Discussionmentioning
confidence: 98%
“…Although most studies report that AN is a clinical indicator of underlying insulin resistance, some researchers believe that AN is not an independent marker and as such all children with a BMI standard deviation score above or equal to 3 should be screened for hyperinsulinemia ( 24 , 25 ). Numerous studies have suggested that in children with both AN and obesity, the incidence and positive predictive value of insulin resistance increases compared to either factor alone ( 19 , 26 , 27 ).…”
Section: Fasting Insulin Levels and Homeostasis Model Of Insulin Resi...mentioning
confidence: 99%
“…Most cases of malignant AN (60%) are detected at the time of diagnosis, and to a lesser extent, before (20%) or after (20%) the diagnosis of cancer [ 1 , 5 ]. The onset of AN in metabolic causes is not well documented in the literature; however, its association with obesity and insulin resistance has been used to allow early intervention and prevent progression to type 2 diabetes [ 6 ]. The pathophysiology of AN is not fully understood, but it has been linked to a multifactorial combination of elevated levels of insulin-like growth factor and transforming growth factor alpha and its action on epidermal growth factor receptors on susceptible cells, leading to hyperproliferation of keratinocytes and fibroblasts [ 7 ].…”
Section: Introductionmentioning
confidence: 99%